EVALUATION OF PROFESSIONAL TEACHER PERFORMANCE PROGRAM IMPLEMENTATION - ENDIANI, Een (Journal of Education and Leadership in Education, 2023)
The purpose of this study is to know and analyze: Design, Installation, Process, Product and Program comparison of the implementation of professional teacher performance programs. Researchers conducted research on evaluating the implementation of professional teacher performance through the discrepancy model. This model contains context evaluation, input evaluation, process evaluation and product evaluation. Based on the results of the study, it is known that: 1) Evaluation of teacher teaching performance design in the planning aspect still found gaps, especially in the aspect of formulating learning objectives in RPP and preparing teaching materials in a coherent, logical, contextual and up-to-date manner, as well as planning learning activities that were still found one research subject that was not in accordance with the indicators. For other aspects it is in accordance with the indicators; 2) Evaluation of teacher teaching performance installations has been prepared in accordance with established teacher teaching performance appraisal standards; 3) Evaluation of the teacher teaching performance process in the aspect of learning implementation of seven indicators, only two still show gaps, namely mastery of subject matter and the application of effective learning approaches or strategies while the other indicators are in accordance with the indicators of the implementation of learning activities (no gaps); 4) Evaluation of teacher performance results in the aspect of learning assessment has been in accordance with the indicators or it can be said that there is no gap at all.